SAT0132 Presence of Psychological, Sexual and Sleep Disorders in Patients with Rheumatoid Arthritis. (15th July 2016) - Santos-Moreno, P.; Villarreal, L.; Ballesteros, G.; Bello, J.; Castillo, E.; Giraldo, R.; Gomez, D.; Aza, A.; Lopez, A.; Cardozo, A.; Palacio, N.; Castro, C.; et al.
Abstract : Background: The rheumatoid arthritis (RA), as known, causes inability in various performance areas mostly in the musculoskeletal, but few is known about psychological, sleep and sexual problems. Objectives: The aim of this study is to describe the socio-demographic profile of patients with RA in specialized RA clinic in Colombia, where we identified disorders in areas besides the physical or musculoskletal, like psychological, sexual and sleep. Methods: A descriptive study was performed in a specialized clinic dedicated to care patients with RA. 1298 RA patients were included in the study, which were seen by the area of psychology; information was collected through semi-structured interviews and non-probability sampling, also using classificatory criteria of pathologies described in CIE 10 diagnostic manual, applying descriptive epidemiology for continuous variables, measure of central tendency and dispersion for qualitative and categorical variables through percentages and averages. Results: Total sample of patients was 1298, 1048 (80%) were women and 250 (19%) were men. Patients had a DAS28 2.6 in average ± 1.1; mean age was 55.1 ± 8.8 years; 58% of patients were medium socio-economical level and the 34% were low socio-economical level; 59% were married, 18% were divorced, 14% is single and 6% were widowed. Related with the occupation, 25% were retired because age and 10% had handicap retirement pay; 24% were dedicated to housekeeping and 35% were working. Related to education 6% were illiterate, 44% had elementary school, 33% high school, 8% had a technical degree and only 7% had college level. According to CIE-10 739 patients (57%) had psychological disorders, 279 patients (21%) had sexual and 373 (28%) had sleep disorders. Conclusions: According to these findings there is a high prevalence of patients with low-medium socio-economical levels in RA which shows a possible correlation of a socio-demographic unfavorable situation with presence of disease. Also there are high rates of psychological, sexual and sleep comorbidities, which implies that measures must be implemented in order to improve these areas of performance in patients with RA. Disclosure of Interest: None declared